Aktif dan Higienis: Program Pengabdian Masyarakat dalam Mendorong Perilaku Sehat di Desa Ramea Kabupaten Pandeglang - Febsi, Yania; Hasby, Rizal Maulana; Fajar, Fajar; Novianti, Annisa; Shihab, Gilang Syahdu; Fitriani, Ratna Rizky; Oktaviana, Tri Lulu; Rizqia, Namira Rahmi; Fitra, Fitra; Oktaviana, Rio Ahmad; Sofiani, Fini (Abdimas Universal, 2025)
Healthy and hygienic behaviors are crucial for improving public health, particularly in rural areas. This community service program aims to promote healthy behaviors in Ramea Village, Pandeglang Regency, through regular exercise and handwashing activities. Exercise sessions are held at the Ramea Village field near the student post, involving community members of all ages, both young and old. Meanwhile, handwashing activities are conducted at MI Darul Huda Elementary School. The method involves direct socialization with the community and school children, facilitated by KKM students. The results of this program indicate that the Ramea Village community responded positively and enthusiastically participated in the exercise sessions held every Sunday and the handwashing practices among elementary school children, leading to an increased awareness and adoption of healthy living behaviors within the community.